2022
DOI: 10.1155/2022/3568263
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Approach to Mitigating Solar Photovoltaic Power Penetration Effects in a Microgrid

Abstract: High solar photovoltaic (PV) penetration in the electrical grid can result in undesired effects on the voltage quality, leading to line loss and voltage magnitude increases. One of the main criteria to ensure the safe penetration of high-power solar systems in the main grid is maintaining an acceptable voltage magnitude when a disturbance occurs (e.g., 0.95 and 1.05 per unit) with respect to total installed power generation capacity of PV power plants. This manuscript analyzes the effects of high solar PV pene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The United States is currently experiencing a substantial surge in demand for renewable energy sources, primarily driven by the need to address escalating environmental concerns, combat climate change, and reduce dependence on finite fossil fuels [1][2][3][4][5][6][7]. The International Energy Agency (IEA) reported that in 2019, renewable energy accounted for approximately 11% of the total U.S. energy consumption, signifying a notable shift towards sustainable alternatives [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The United States is currently experiencing a substantial surge in demand for renewable energy sources, primarily driven by the need to address escalating environmental concerns, combat climate change, and reduce dependence on finite fossil fuels [1][2][3][4][5][6][7]. The International Energy Agency (IEA) reported that in 2019, renewable energy accounted for approximately 11% of the total U.S. energy consumption, signifying a notable shift towards sustainable alternatives [8].…”
Section: Introductionmentioning
confidence: 99%
“…Solar 2024, 4 247 Within the spectrum of renewable energy solutions, solar photovoltaic (PV) power has emerged as a frontrunner in addressing climate change and bolstering alternative energy adoption across the USA [7,9,10]. The International Renewable Energy Agency (IRENA) reported that in 2018, the levelized cost of electricity (LCOE) for utility-scale solar PV in the United States plummeted to just 3.7 cents per kilowatt-hour (kWh), underlining its economic viability and environmental benefits [11].…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, integrating photovoltaic system with the grid has gained attention considering the limitation of space and management of battery banks [1]. Grid synchronization of photovoltaic systems incorporate power electronic converters with high-switching speed.…”
Section: Introductionmentioning
confidence: 99%